Improving the friction performance of TiAlSiN-coated hard alloy through pulsed magnetic field treatment - Zhang Lin; Yan Qiaosong; He Asha; Chen Zhe; Wu Mingxia; Yang Yi; Liu Jian (Manufacturing Review)
For processing the difficult-to-cut materials, TiAlSiN coatings have been widely applied to machining tools. Pulse magnetic field treatment, as a novel, fast, and environmentally friendly post-treatment method, can directly modify the finished TiAlSiN-coated tools without causing physical damage. This study investigates the wear resistance of pulse magnetic field-treated TiAlSiN-coated carbide samples under both dry and lubricated friction conditions. Results show that pulse magnetic field-treated TiAlSiN-coated samples exhibit improved wear resistance and friction reduction in both friction environments. In dry friction conditions, the coating's coefficient of friction decreased by 13.73%, resulting in a more stable friction process. In lubricated conditions, the coefficient of friction decreased by 23.46%. Due to the effects of the pulse magnetic field, the hardness of the coating and substrate increased by 6.58% and 3.7%, respectively. The bonding phase Co in the carbide substrate exhibited phase transformation and increased defect density, such as dislocations. These changes enhanced the bonding strength at the coating/substrate interface, thereby improving its mechanical performance and tribological behavior.